Questions à Marie-Clémence Andriamonta-Paes sur le film-documentaire Fahavalo (Cahiers d’histoire.)
On October 7, 2023, on the occasion of the « Rendez-vous de l’histoire in Blois », the Cahiers d’histoire co-organised the screening of the documentary Fahavalo. Madagascar 1947, released in 2018, in the presence of Marie-Clémence Andriamonta-Paes, its director. This film is the result of a long work of research and collecting the memory of the last Malagasy witnesses of the uprising of 1947-1948 against the French colonial power. The Cahiers d’histoire review the genesis of a remarkable and essential work, which aims to bring out of oblivion this unknown episode of anti-colonial struggles.